2006
DOI: 10.1016/j.molcel.2006.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptosome Activates Caspase-9 by Dimerization

Abstract: The apical protease of the human intrinsic apoptotic pathway, caspase-9, is activated in a polymeric activation platform known as the apoptosome. The mechanism has been debated, and two contrasting hypotheses have been suggested. One of these postulates an allosteric activation of monomeric caspase-9; the other postulates a dimer-driven assembly at the surface of the apoptosome--the "induced proximity" model. We show that both Hofmeister salts and a reconstituted mini-apoptosome activate caspase-9 by a second-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
197
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(207 citation statements)
references
References 36 publications
8
197
2
Order By: Relevance
“…[48][49][50] These recruitment platforms integrate cellular signals, promote dimerization of initiator caspases and lead to the formation of an active enzyme proficient to initiate specific signaling cascades. 51,52 These platforms are multiprotein complexes consisting of various molecules assembled on a central scaffold protein that characteristically possesses three main domains: a region involved in ligand sensing, a domain driving oligomerization and a domain involved in recruiting the caspases. The prototypical example is the apoptosome scaffold protein Apaf-1.…”
Section: Activation Of Inflammatory Caspases: Inflammasomes and Othermentioning
confidence: 99%
“…[48][49][50] These recruitment platforms integrate cellular signals, promote dimerization of initiator caspases and lead to the formation of an active enzyme proficient to initiate specific signaling cascades. 51,52 These platforms are multiprotein complexes consisting of various molecules assembled on a central scaffold protein that characteristically possesses three main domains: a region involved in ligand sensing, a domain driving oligomerization and a domain involved in recruiting the caspases. The prototypical example is the apoptosome scaffold protein Apaf-1.…”
Section: Activation Of Inflammatory Caspases: Inflammasomes and Othermentioning
confidence: 99%
“…The most commonly used tools include caspase-specific anti-sera as well as fluorogenic substrates and inhibitors. Unfortunately, antibody reagents often do not provide an accurate measure of caspase activity since several caspase family members (caspases 8/10 and 9) do not require proteolytic processing for activation [2,3]. Furthermore, recent evidence suggests that caspase-7 (an executioner caspase) activation occurs via a catalytically active full-length intermediate that cannot be differentiated from the non-cleaved inactive zymogen using antibodies [4,5].…”
Section: Dear Editormentioning
confidence: 99%
“…A faint band of 39 kDa caspase-9 was also detectable, reflecting procaspase-9 processing by caspase-3, which increased further as the apoptosis reactions progressed [26]. Since auto-processing of procaspase-9 occurs by its activation through homo-dimerization, the 37-kDa form was thought to signify induction of the caspase-9 pathway [7,19,20,22]. This initial experiment suggested that +/+ and fog/fog cells were equally capable of capase-9 activation in response to the oxidative stress.…”
Section: Detection Of Caspase-9 Activation In Fog/fog and +/+ Micementioning
confidence: 99%
“…In fact, procaspase-9 is able to homo-dimerize to gain its enzyme activity in the absence of Apaf-1 as evidenced by bacterial expression systems, in vitro translation and biochemical analyses [7,[19][20][21][22]. More importantly, procaspase-9 is dimerized by higher concentrations of kosmotropes, salts able to stabilize proteins, such as 1 M citrate [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation